Liquidity coverage ratios and monetary policy credit in the time of Corona - Viktoriya Gocheva; Yvo Mudde; Jens Tapking (European Central Bank (ECB), 2022)
When a bank receives credit from the central bank, its Liquidity Coverage Ratio (LCR) changes. In most cases, the LCR increases. We investigate how this LCR boost from central bank credit affects banks' behaviour, looking at the euro area during the Corona year 2020. Our theoretical and empirical analyses suggest that banks that get strong LCR boosts from central bank credit tend to take actions that reduce their LCRs. In this sense, banks consume their LCR boosts. In terms of policy conclusions, our analysis suggests that central bank credit operations can provide strong incentives for banks to take actions that reduce their LCRs. Such actions, which could include the provision of additional credit and a shortening of the maturity structure of the liabilities of the banks, plausibly have an impact on the real economy. As such, our analysis reveals what may be called a "LCR channel" of monetary policy transmission.
Keywords: E52; E58; G28; 330; Liquidity Coverage Ratio; central bank credit operations; monetary policy transmission; Corona pandemic